2022
DOI: 10.1177/14680874221131117
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the methane and producer gas blends in an optical spark ignition engine: Combustion characteristics, thermodynamics and emissions

Abstract: Thermal processes and power generation systems may employ producer gas generated through gasification as an alternative to replace natural gas with lower carbon footprint. However, pure producer gas in engines is associated with a significant power derating that can be mitigated by blending it with other biofuels. This work evaluated the effects of methane and producer gas blends on the performance of a SI engine. The additions of methane were 10%, 25% and 50% on a molar basis. The results demonstrated that ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Optically accessible engines provide results that can be used to benefit both endeavors, thereby enabling the development of advanced solutions for the optimization of engines, such as the ones developed by Irimesco [19] or Merola et al [20], which can be applied in the development of more efficient commercial engines. The authors of this work have shown in recent studies that the addition of methane to syngas will favor the stability of the flame and the conversion efficiency [15], while the addition of hydrogen will improve not only the flame stability but also its emissions [16,21,22]. The addition of hydrogen to syngas also improves the propagation stability of lean operation [21].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Optically accessible engines provide results that can be used to benefit both endeavors, thereby enabling the development of advanced solutions for the optimization of engines, such as the ones developed by Irimesco [19] or Merola et al [20], which can be applied in the development of more efficient commercial engines. The authors of this work have shown in recent studies that the addition of methane to syngas will favor the stability of the flame and the conversion efficiency [15], while the addition of hydrogen will improve not only the flame stability but also its emissions [16,21,22]. The addition of hydrogen to syngas also improves the propagation stability of lean operation [21].…”
Section: Introductionmentioning
confidence: 94%
“…Since the specific energy of syngas is lower than conventional fossil fuels, consequently, the engine's output will be relatively low when syngas is used to feed it [9,13]. To overcome this issue, some methodologies can be applied, such as using superchargers, increasing the compression ratio [9,14], or blending the syngas with other higher-ranked fuels, such as methane [15], hydrogen [16,17], or others [18]. Currently, the primary focus of research on syngas-powered engines is centered around optimizing the engines to the fullest potential and enhancing numerical models [14].…”
Section: Introductionmentioning
confidence: 99%